Thinking Together Urban Conservation With Urban Modernization In The Process Of Urban Transformation: The Possibilities Of "Historic Urban Landscape" Concept - İclal Dinçer (Iconarp International Journal of Architecture and Planning, 2013)
Today, the big cities that are centers of innovation and creativity offer employment and training opportunities for people on the one hand, and are faced to face to uncontrolled urbanization on the other. One of the main problems of these cities is socio-cultural and spatial harmony between urban heritage and new developments. It should be recognized that it is difficult to preserve both the tangible and intangible heritage and sustainable development together with providing the quality of urban life. This article will discuss the "historic urban landscape" concept that is one of the approaches in the long term evolution of conservation and reconstruction of cities. In this evolution process, concepts of urban conservation, environmenta protection, urban archaeology, cultural landscape and the value o cultural heritage for society are the important milestones. Within this approach "historic urban landscape", decision-making processes needs to evolve towards the partnerships of state, market and civil society actors through negotiation and cooperation between them. In the article three examples from Istanbul are examined.